2021
DOI: 10.3390/s21020375
|View full text |Cite
|
Sign up to set email alerts
|

Online Extraction of Pose Information of 3D Zigzag-Line Welding Seams for Welding Seam Tracking

Abstract: Three-dimensional (3D) zigzag-line welding seams are found extensively in the manufacturing of marine engineering equipment, heavy lifting equipment, and logistics transportation equipment. Currently, due to the large amount of calculation and poor real-time performance of 3D welding seam detection algorithms, real-time tracking of 3D zigzag-line welding seams is still a challenge especially in high-speed welding. For the abovementioned problems, we proposed a method for the extraction of the pose information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Experimental results showed that the average deviations in the X direction were reduced to 0.387 mm and 0.429 mm after precise positioning of the feature points, respectively. Some spatial welds are just oriented towards the relative regular curves such as spirals and coherent lines [14,15]. Not much attention is paid to the three-dimensional (3D) complex welding seams with an arbitrary shape.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental results showed that the average deviations in the X direction were reduced to 0.387 mm and 0.429 mm after precise positioning of the feature points, respectively. Some spatial welds are just oriented towards the relative regular curves such as spirals and coherent lines [14,15]. Not much attention is paid to the three-dimensional (3D) complex welding seams with an arbitrary shape.…”
Section: Introductionmentioning
confidence: 99%
“…[22] introduced deep learning to improve weld recognition accuracy. [23] proposed a method of density-based clustering point cloud segmentation to acquire the weld seam position information. However, the extraction of laser stripe feature points would be affected by various interferences directly during image acquisition.…”
Section: Introductionmentioning
confidence: 99%
“…The welding velocity is a variable to take into account in the welding seam position. Hong et al [11] generated a 3D welding seam by the laser displacement sensor. It was segmented using a Density-Based Spatial Clustering of Applications with Noise algorithm.…”
Section: Introductionmentioning
confidence: 99%